Reflections on Angela Merkel's career as chancellor of Germany and the Greek financial odyssey - George K. Zestos; Harrison Whittleton; Alejandro Fernandez-Ribas (Levy Economics Institute of Bard College, 2022)
Angela Merkel is the second-longest-serving chancellor of modern Germany, with more than 16 years in office. During her tenure there were many years of economic stability, but there were also years of domestic, EU, and geopolitical tensions. Merkel inherited an economy that was recovering after the launching of probusiness policies known as the Hartz I IV Reforms, introduced by the government of the previous chancellor, Gerhard Schröder. Chancellor Merkel was criticized for mishandling the eurocrisis, as she failed to declare support for the financially distressed eurozone countries. Instead she convinced EU officials and country leaders to adopt a contractionary fiscal policy in the midst of a recession. As a result of the austerity measures, Merkel became popular among the German taxpayers and voters. This triggered credit rating agencies to downgrade the government bonds of the periphery eurozone countries and investors to sell these bonds, driving their prices to zero. Periphery eurozone countries came close to bankruptcy but were jointly bailed out by the EU and the IMF, though this prolonged the crisis. As a result of the imposed austerity, which was unnecessary and avoidable, millions of people became unemployed and experienced poverty, loss of dignity, and humiliation and Greece was the country hit hardest. For Merkel, placing national interests above EU interests was the most important mistake in her career; it took, however, a bigger crisis (i.e., the COVID-19 pandemic), to convince Merkel to place EU interests above national interests.
Keywords: F30; N10; N14; O52; P16; 330; Angela Merkel; Eurocrisis; Austerity; COVID-19; Greece